Description of Labiduris Argentinensis sp. Nov. (Nematoda: Cosmocercoidea: Atractidae) a new species of nematode in Chelonoidis Chilensis gray, 1870 (Testudines: Testudinidae) for Argentina - González-Rivas, Cynthia J. (2024)
We describe a new species of Labiduris (Thapar, 1925) (Cosmocercoidea: Atractidae) collected from the long intestine of the land turtle Chelonoidis chilensis Gray 1870 in Argentina. Labiduris argentinensis sp. nov. differs from Labiduris gulosa (Rudolphi, 1819) (the only valid species of the genus), by the type and geographic distribution of the host, position of the excretory pore, body size and tail of the male and female nematodes. The new species has an excretory pore at the level of the middle widening of the esophagus, smaller body size, short and truncated tail, and is found in a terrestrial turtle with restricted distribution in Argentina. These characteristics of the new species are different from those of L. gulosa, which has an excretory pore in front of the bulb and a long, pointed tail and a larger body. The new species L. argentinensis sp. nov. represents the second valid species for the genus Labiduris.